2015
DOI: 10.1523/jneurosci.1965-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Hearing Loss in Mice Carrying a Mutation inUsp53

Abstract: Disordered protein ubiquitination has been linked to neurodegenerative disease, yet its role in inner ear homeostasis and hearing loss is essentially unknown. Here we show that progressive hearing loss in the ethylnitrosourea-generated mambo mouse line is caused by a mutation in Usp53, a member of the deubiquitinating enzyme family. USP53 contains a catalytically inactive ubiquitin-specific protease domain and is expressed in cochlear hair cells and a subset of supporting cells. Although hair cell differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 71 publications
3
70
0
Order By: Relevance
“…In the case of claudins-9 and -14, in vitro recordings have shown that the junctions become leaky, likely allowing K + to enter the organ of Corti and potentially killing hair cells through K + toxicity. There is little evidence, however, tying compromised tight junctional proteins within the reticular lamina to EP reduction (but see Kazmierczak et al 2015). The EP appears to be sensitive only to large changes in the ion-tightness of the reticular lamina, or to overt tears as may be caused by more intense noise than we applied (Salt and Konishi 1979;Melichar et al 1980;Hirose and Liberman 2003).…”
Section: Genes and Processes That Establish Or Modulate The Epmentioning
confidence: 90%
“…In the case of claudins-9 and -14, in vitro recordings have shown that the junctions become leaky, likely allowing K + to enter the organ of Corti and potentially killing hair cells through K + toxicity. There is little evidence, however, tying compromised tight junctional proteins within the reticular lamina to EP reduction (but see Kazmierczak et al 2015). The EP appears to be sensitive only to large changes in the ion-tightness of the reticular lamina, or to overt tears as may be caused by more intense noise than we applied (Salt and Konishi 1979;Melichar et al 1980;Hirose and Liberman 2003).…”
Section: Genes and Processes That Establish Or Modulate The Epmentioning
confidence: 90%
“…HEK293 cells were transiently transfected using X-tremeGENE 9 DNA transfection reagent (Roche) according to the manufacturer’s instructions. Cell lysis, immunoprecipitations with anti-GFP antibody (rabbit, Sigma) or anti-Flag antibody (mouse, Sigma) and Western blot analysis were carried out as described (Kazmierczak et al, 2015), except that cellular extracts were prepared in 50 mM TrisHCl, pH 7.6, 150 mM NaCl, 1% NP-40 and immunocomplexes washed three times in 50 mM TrisHCl, pH 7.6, 150 mM NaCl, and 0.25% NP-40. The blots were probed with anti-GFP (rabbit, Sigma), anti-Flag (mouse, Sigma) and anti-HA-HRP (rat, Roche) antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Reverse transcription and qPCR was performed as described previously (Kazmierczak et al, 2015). Primers recognizing Pgk1 were: forward, 5′-CAACAACATGGAGATTGGCACA, reverse 5′-ACAGTAGCTTGGCCAGTCTTG; and for Pjvk : forward CGGTGCCTTCGACATTTGTG, reverse 5′-GCGTCCATCACTCTCCTGTT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations suggest that the disordered ubiquitination of ZO proteins might alter the barrier properties of TJs in the inner ear, leading to a loss of inner ear homeostasis and deafness. 96…”
Section: Zo-2 and Its Relationship With Hearing Impairment And Apoptosismentioning
confidence: 99%